A study of influential and effective supervisory roles as perceived by the elementary teachers in Newfoundland and Labrador - Oldford, William Ross (1972)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1972. Education Bibliography: leaves 137-141.